The impact of psychological engineering techniques in Enhancment Strategic Ambidxterity: Analytical Research of views of a Sample of collge members Private universities and Colleges working in Governorate of the Babylone - Hurajah ALHasnawi, Hussein; Adnan Al-Sanjari, Hind (Iraqi Journal for Administrative Sciences, 2024)
The present research seeks to determine the nature of the relationships of influence and the link between psychological engineering techniques and strategic ambidexterity at the level of universities and private colleges in the province of Babylon to achieve this, the measurement of psychological engineering techniques was based on eight sub-dimensions (Flexibility, Anchoring, Elicitation, Modeling, Individual Differences, Leadership, Establishing Rapport, and Emotional &Cognitive Boosters) While strategic ambidexterity was measured by two dimensions (Exploratory strategy, Exploitative strategy), the Descriptive and Analytical Methodology was used to Present the research topics, The sample was (200) faculty members. A variety of statistical methods and tools have been used test, Assertive factor analysis, descriptive statistics,(pearson) correlation analysis, structural equation modeling,& path analysis & these methods have been used on statistical programs (Amos,V,23, SPSS V.25), The research has reached a number of conclusions, the most important of which: improving the level of psychological engineering techniques among faculty members in the researched universities and colleges in turn enhances the level of strategic ambidexterity in general, ,the research concluded with a number of appropriate recommendations.